Sistematic Literature Review: Analisis Pentingnya Kepemimpinan Pada Keselamatan Operasi Penerbangan - Waluyo Setyo Pramono; Surtiningtyas, Sri Rahayu (Politeknik Penerbangan Indonesia Curug, 2024)
This study explores the impact of leadership on aviation operation safety through a Systematic Literature Review (SLR) method. In the aviation industry, safety is a top priority that requires contributions from all employees and effective leadership. Safety leadership is defined as the ability of leaders to promote a safety culture through consistent actions, communication, and policies. This research aims to determine whether leadership has a significant impact on aviation operation safety and to identify influential leadership factors. SLR was chosen for its ability to provide a comprehensive and evidence-based evaluation of existing literature, thereby reducing researcher bias. The search process was conducted using Google Scholar, Research Gate, and Science Direct, with the keywords